Adsorbent for immersion cooling
Patent Information
- Application Number
- CN202280052644.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-04
- Filing Date
- 2022-06-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-06
AI Technical Summary
然而,此类常规过滤器和吸附剂必须频繁更换,这是昂贵的,并且可能导致不期望的维护和停机时间
[0033]在一些方面,本文所描述的技术涉及一种系统,其进一步包含含有一种或多种导电污染物的电子组件。
Smart Images

Figure CN117715699B_ABST
Abstract
Description
[0001] Cross-referencing related applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 196,892, filed on June 4, 2021, which is hereby incorporated in its entirety by reference. Technical Field
[0003] This disclosure generally relates to methods and systems for purifying coolants. Background Technology
[0004] As client computing demands and data center density continue to increase, the heat dissipation requirements for electronic components such as microprocessors, chipsets, graphics processing units (GPUs), and memory modules are also rising. Conventional client computing devices and data centers are air-cooled, typically using radiators, heat sinks, and fans to deliver cool air to electronic components and remove waste heat through conduction and convection. Such devices and technologies have drawbacks. While air is electrically insulating and non-corrosive, its large volume, given its heat capacity, means that delivering cool air to electronic components, removing heated exhaust gases, cooling heated exhaust gases (usually via air conditioning), and recirculating the cool air are mechanically energy-intensive.
[0005] In contrast, immersion cooling encases the electronic components in a thermally conductive but electrically insulating (dielectric) coolant. Thus, the coolant removes waste heat from the electronic components by transferring heat from them to the coolant. The now-heated coolant then enters a heat exchanger, where it is cooled by proximity to another fluid, such as air or water. The coolant is electrically insulating to ensure safe contact with leads, traces, surface mount pads, solder, and other electronic components exposed and energized during normal operation.
[0006] Typically, immersion cooling systems consist of electronic devices to be cooled, submerged in a coolant. Over time, various material components of the electronic devices may leach into the coolant. While the coolant itself is electrically insulating, contaminants can be introduced from solder and metal components, as well as from elastomers, fluxes, corrosion inhibitors, PVC insulation, foams, adhesives, and their reaction products with the coolant. These contaminants can increase the conductivity of the coolant. Such contaminants that increase the conductivity of a fluid are called conductive contaminants, and they are typically introduced into the coolant through leaching from the electronic components submerged in the coolant or by other means. Because increased conductivity is undesirable for coolants that must maintain electrical insulation, such conductive contaminants must be removed.
[0007] Currently, filtration systems exist for immersion cooling systems. However, such conventional filters and adsorbents must be replaced frequently, which is costly and can lead to undesirable maintenance and downtime. For example, conventional adsorbents containing adsorbent material are provided in the housing in an amount approximately five times the expected mass of contaminants in the coolant. Optimization of the adsorbent, particularly by increasing the efficiency and adsorption capacity of the adsorbent material contained therein, and the adsorbent contained in the filter, will represent progress in the industry, reducing costs associated with immersion cooling. Both of these aspects reduce the need for adsorbent replacement and also impact the increased efficiency achieved by using coolants with higher purity. Such adsorbents should not additionally introduce contaminants into the coolant itself. Summary of the Invention
[0008] The following shows an overview of several embodiments according to this disclosure.
[0009] In some aspects, the technology described herein relates to a method for purifying a coolant containing one or more conductive contaminants, the method comprising: contacting the coolant with an adsorbent, thereby causing the adsorbent to adsorb the one or more conductive contaminants, wherein the adsorbent comprises an adsorbent material having a bulk oxygen content of about 1 wt.% to about 5 wt.%, a moisture level of up to about 1.5 wt.%, and a molasses number of at least about 150, wherein the adsorbent material comprises activated carbon.
[0010] In some respects, the technology described herein relates to a method in which the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nut, macadamia nut, dende nut, peach pit, cherry pit, olive pit, walnut shell, wood, bagasse, rice husk, corn husk, wheat husk, polymer, resin, petroleum bitumen, and other carbonaceous materials.
[0011] In some respects, the techniques described herein relate to a method in which the adsorbent material is formed by calcining a carbonaceous material at a temperature of at least about 500°C under an inert atmosphere.
[0012] In some respects, the techniques described herein relate to a method in which the weight iodine number of the adsorbent material is at least about 850 mg / g.
[0013] In some respects, the techniques described herein relate to a method in which the weight iodine number of the adsorbent material is at least about 1100 mg / g.
[0014] In some respects, the techniques described herein relate to a method in which the adsorbent has been treated to prevent the reintroduction of oxygen.
[0015] In some respects, the techniques described herein relate to a method in which the treatment of the adsorbent to prevent the reintroduction of oxygen comprises one or more of the following: purging the adsorbent material with an inert atmosphere; placing the adsorbent within a housing containing an oxygen removal compound; and mechanically removing oxygen from the housing containing the adsorbent.
[0016] In some respects, the techniques described herein relate to a method in which the coolant comprises one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof.
[0017] In some respects, the techniques described herein relate to a method in which the coolant has a boiling point of about 34°C to about 175°C and a dielectric constant of less than about 10 at 1 kHz.
[0018] In some respects, the techniques described herein relate to a method in which the kinematic viscosity of the coolant does not exceed about 0.8 cSt.
[0019] In some respects, the techniques described herein relate to a method that further comprises contacting an electronic component with a coolant and allowing conductive contaminants to diffuse from the electronic component into the coolant.
[0020] In some respects, the techniques described herein relate to a method that further includes filtering the coolant through a size-restricted filter.
[0021] In some aspects, the technology described herein relates to a system for purifying a coolant containing one or more conductive contaminants, the system comprising: a housing containing an adsorbent comprising an adsorbent material having a bulk oxygen content of about 1 wt.% to about 5 wt.%, a moisture level of up to about 1.5 wt.%, and a molasses number of at least about 150; at least one inlet, or at least one outlet, or at least one inlet and at least one outlet communicating with the adsorbent; and a tank containing the coolant such that at least a portion of the coolant is in contact with the adsorbent.
[0022] In some respects, the technology described herein relates to a system in which the adsorbent comprises an adsorbent material that is itself activated carbon.
[0023] In some respects, the technology described herein relates to a system in which the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nuts, macadamia nuts, palm nuts, peach pits, cherry pits, olive pits, walnut shells, wood, bagasse, rice husks, corn husks, wheat husks, polymers, resins, petroleum bitumen, and other carbonaceous materials.
[0024] In some respects, the technology described herein relates to a system in which the adsorbent material is formed by calcining a carbonaceous material at a temperature of at least about 500°C under an inert atmosphere.
[0025] In some respects, the techniques described herein relate to a system in which the weight iodine number of the adsorbent material is at least about 850 mg / g.
[0026] In some respects, the techniques described herein relate to a system in which the weight iodine number of the adsorbent material is at least about 1100 mg / g.
[0027] In some respects, the techniques described herein relate to a system in which the adsorbent has been purged with nitrogen to prevent the reintroduction of oxygen.
[0028] In some respects, the technology described herein relates to a system in which the adsorbent is inertly filled or vacuum-filled in the housing.
[0029] In some respects, the technology described herein relates to a system that further comprises a pump for delivering the coolant through the adsorbent.
[0030] In some respects, the technology described herein relates to a system in which the coolant comprises one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof.
[0031] In some respects, the technology described herein relates to a system in which the coolant has a boiling point of about 34°C to about 175°C, a freezing point of about -38°C to about -138°C, and a dielectric constant of less than about 10 at 1 kHz.
[0032] In some respects, the technology described herein relates to a system in which the kinematic viscosity of the coolant does not exceed about 0.8 cSt.
[0033] In some respects, the techniques described herein relate to a system that further comprises electronic components containing one or more conductive contaminants.
[0034] In some respects, the technology described herein relates to a system in which the electronic components are housed within a data center.
[0035] In some respects, the technology described herein relates to a system that further comprises a size exclusion filter connected downstream of the housing containing the adsorbent.
[0036] In some aspects, the technology described herein relates to a composition for purifying a coolant containing one or more conductive contaminants, the composition comprising: an adsorbent comprising an adsorbent material having a bulk oxygen content of about 1 wt.% to about 5 wt.%, a moisture level of up to about 1.5 wt.%, and a molasses number of at least about 150, wherein the adsorbent material comprises activated carbon.
[0037] In some respects, the technology described herein relates to a composition in which the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nuts, macadamia nuts, palm nuts, peach pits, cherry pits, olive pits, walnut shells, wood, bagasse, rice husks, corn husks, wheat husks, polymers, resins, petroleum bitumen, and other carbonaceous materials.
[0038] In some respects, the techniques described herein relate to a composition in which the contact pH of the adsorbent material is from about 6.5 to about 12.
[0039] In some respects, the techniques described herein relate to a composition in which the weight iodine number of the adsorbent material is at least about 850 mg / g.
[0040] In some respects, the techniques described herein relate to a composition in which the weight iodine number of the adsorbent material is at least about 1100 mg / g.
[0041] In some respects, the techniques described herein relate to a composition in which the adsorbent has been treated to prevent the reintroduction of oxygen.
[0042] In some respects, the technology described herein relates to a method for preparing an adsorbent for purifying a coolant containing one or more conductive contaminants, the adsorbent comprising an adsorbent material, the method comprising: calcining a precursor adsorbent material to form an adsorbent material having a bulk oxygen content of about 1 wt.% to about 5 wt.%, a moisture level of up to about 1.5 wt.%, and a molasses number of at least about 150, wherein the adsorbent material comprises activated carbon.
[0043] In some respects, the technology described herein relates to a method in which the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nuts, macadamia nuts, palm nuts, peach pits, cherry pits, olive pits, walnut shells, wood, bagasse, rice husks, corn husks, wheat husks, polymers, resins, petroleum bitumen, and other carbonaceous materials.
[0044] In some respects, the techniques described herein relate to a method in which calcination occurs at a temperature of at least about 500°C.
[0045] In some respects, the techniques described herein relate to a method that further includes treating the adsorbent material to prevent the reintroduction of oxygen and moisture.
[0046] In some respects, the techniques described herein relate to a method in which treating the adsorbent to prevent the reintroduction of oxygen comprises one or more of the following: purging the adsorbent material with an inert atmosphere; placing the adsorbent within a housing containing an oxygen removal compound; and mechanically removing oxygen from the housing containing the adsorbent.
[0047] This disclosure provides a method for purifying a coolant for electronic components, the method comprising: contacting the coolant with an adsorbent, wherein the adsorbent is characterized by a molasses number of at least 330 by weight. In any embodiment, the adsorbent may be activated carbon, for example, formed from: bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nuts, macadamia nuts, palm nuts, peach pits, cherry pits, olive pits, walnut shells, wood, bagasse, rice husks, corn husks, wheat husks, polymers, resins, petroleum asphalt, or other carbonaceous materials. In any embodiment, the adsorbent may be formed by calcining a carbonaceous material at a temperature of at least about 500°C under an inert atmosphere. In any embodiment, the adsorbent may exhibit an adsorption capacity of about 0.2 g / cm³. 3 Approximately 1 g / cm 3 The apparent density. In any embodiment, the adsorbent may exhibit an iodine number of at least about 850 mg / g, such as at least about 1100 mg / g. In any embodiment, the water content of the adsorbent may be less than about 15 wt.%. In any embodiment, a suitable adsorbent has been treated to remove oxygen-containing surface groups, for example, by purging the adsorbent with an inert atmosphere, placing the adsorbent in a housing containing an oxygen scavenging compound, and mechanically removing oxygen from the housing containing the adsorbent. In any embodiment, the treatment may include purging the adsorbent with an inert atmosphere.
[0048] The adsorbent can be used to purify a coolant, which may include one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof, optionally having a boiling point of about 34°C to about 175°C, and a dielectric constant of less than about 10 at 1 kHz. In any embodiment, a suitable coolant may exhibit a kinematic viscosity of no more than about 0.8 cSt.
[0049] In any embodiment, the electronic component cooled by the coolant can be a printed circuit board (PCB). Cooling can be achieved by bringing the electronic component into contact with the coolant. In any embodiment, the coolant can be filtered using a size-restricted filter.
[0050] This disclosure further provides an apparatus assembly or system for purifying a coolant for electronic components, the apparatus assembly or system comprising a coolant and a housing including an adsorbent, wherein the housing is configured to contact the adsorbent with the coolant, and wherein the adsorbent is characterized by a molasses number of at least about 330. In any embodiment, the adsorbent may have been purged with nitrogen to remove oxygen-containing surface groups. In any embodiment, the adsorbent may be provided as an inert filler or a vacuum filler in the housing. The apparatus assembly may further include a pump that delivers the coolant through the adsorbent. In any embodiment, the coolant may be one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof, optionally having a boiling point of about 34°C to about 175°C, a freezing point of about -38°C to about -138°C, and a dielectric constant of less than about 10 at 1 kHz. In any embodiment, the coolant may be used to cool electronic components housed in a data center. Optionally, the coolant may be filtered after passing through the housing, for example by passing the coolant through a size-restricted filter connected downstream of the housing, which includes the adsorbent. Attached Figure Description
[0051] Aspects, features, benefits, and advantages of the embodiments described herein will become apparent from the following description, the appended claims, and the accompanying drawings, in which: Figure 1 A schematic representation of an immersion cooling system is depicted, in which the adsorbent disclosed herein may be used.
[0052] Figure 2 A schematic representation of a two-phase immersion cooling system is depicted, in which the adsorbent disclosed herein may be used.
[0053] Figure 3 A decolorization curve of the adsorbent material was plotted, which measured the relationship between the relative amount of decolorization achieved and the molasses number of the adsorbent material.
[0054] Figure 4 An example of spectral scanning is depicted, illustrating the variation of the transmittance of a molasses filter with the wavelength of light.
[0055] Figure 5The average pH measurements of dried F / S RB or calcined RB sodium nitrate suspensions at common activated carbon concentrations of 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.% are depicted.
[0056] Figure 6 The average pH measurements of dried F / S BGX or calcined BGX sodium nitrate suspensions at common activated carbon concentrations of 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.% were depicted. Detailed Implementation
[0057] Before describing the compositions and methods of the present invention, it should be understood that the scope of the invention is not limited to the specific processes, compositions, or methods described, as these specific processes, compositions, or methods can vary. It should also be understood that the terminology used in the description is for the purpose of describing a particular version or embodiment only and is not intended to limit the scope of the invention, which is limited only by the appended claims. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. Although any methods and materials similar to or equivalent to those described and used herein may be used in the practice or testing of embodiments of the invention, preferred methods, apparatus, and materials are now described. All publications mentioned herein are incorporated by reference with respect to aspects identified as described. Nothing herein should be construed as an admission that the invention is not entitled to prior disclosure by virtue of prior art.
[0058] As used in this document, unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” include the plural references. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. Nothing in this disclosure should be construed as an admission that the embodiments described herein are not entitled to precedence over such disclosure by prior art. As used in this document, the term “comprising” means “including but not limited to.”
[0059] As used herein, the term “about” means ± 10% of the value of the number being used. For example, “about 50%” means within the range of 45% to 55%.
[0060] As used herein, the term "electronic rack" includes any enclosure, frame, rack, compartment, blade server system, etc., containing one or more heat-generating components of a computer system, electronic system, or information technology equipment, and can be, for example, a standalone computer processor with high, medium, or low-end processing power. As used herein, "electronic component" refers to any heat-generating electronic component, such as a computer system or other electronic unit requiring cooling. As an example, an electronic component may include one or more integrated circuit dies and / or other electronic devices to be cooled, including one or more processor dies, memory dies, or memory support dies. As used herein, "data center" refers to a computer installation containing one or more electronic racks to be cooled. As a specific example, a data center may contain one or more rack-mounted computing units, such as server units. A data center may contain random access memory (RAM), one or more processing resources, such as a central processing unit (CPU) or hardware or software control logic, ROM, and / or other types of non-volatile memory. Additional components of a data center may include one or more disk drives, one or more network ports for communication with external devices, and various input and output (I / O) devices, such as a keyboard, mouse, and video monitor. Such data centers, electronic components, or electronic racks often contain one or more systems operable for transmitting data between various electronic components or within the data center, electronic components, or electronic racks themselves. When such systems connect several data centers or electronic racks, they are referred to as data buses within an electronic rack or network. Such systems may also be referred to as networks or computer networks.
[0061] As used herein, the term "adsorbent material" refers to any material that exhibits adsorption properties, absorption properties, or a combination of adsorption and absorption properties. Adsorption properties refer to the adhesion of atoms, ions, or molecules to the surface of a material. Absorption properties mean that atoms, ions, or molecules enter the bulk phase of the material and are retained by said bulk phase. As examples, adsorbent materials include, but are not limited to, activated carbon, reactivated carbon, natural and synthetic zeolites, silica, silica gel, alumina, zirconium oxide, and diatomaceous earth. As used herein, "adsorbent material" is a material whose constituent components are essentially adsorbents and / or absorbents, with only a minimum amount of components that are not non-adsorbents and / or absorbents (e.g., the minimum amount of binder required for activated carbon granules to maintain their shape).
[0062] As used herein, the term "adsorbent" means any composition or complex comprising an adsorbent material in a blend, mixture, complex, or compound with one or more other materials that do not exhibit adsorption or absorption properties. As an example, one embodiment of an adsorbent comprises an activated carbon adsorbent material blended with a thermally conductive filler.
[0063] As used herein, "conductive contaminant" includes any material that, either alone or by acting on other materials, can increase conductivity between circuits, traces, or electronic racks or data centers and other electronic devices or components. Examples of conductive contaminants are not limited and include one or more metal fragments such as aluminum, copper, steel, lead, tin, silver, gold, cadmium, arsenic, selenium, nickel, mercury, zinc, and other metals and their alloys, solder, flux, water, salts, ions, carbon particles, ceramics, conductive polymers, photoresists, etc.
[0064] The adsorbents or adsorbent materials described herein can be characterized by a variety of properties, such as density, porosity and transport structure (by weight molasses number), oxygen level, and mixture level. Standardized methods from ASTM International can be used to characterize many of these different properties. For example, pore (or void) volume can be determined using ASTM D4284-12(2017)e1 or its equivalent. Porosity can be characterized as three general size ranges. Micropores exhibit a pore size less than about 2 nm. Mesopores range in diameter from 2 nm to 50 nm, while macropores have a diameter greater than 50 nm. Particle size distribution can be determined according to ASTM D2862-16 or its equivalent. Moisture content can be determined using ASTM D2867-17 or its equivalent. Weight iodine number can be determined using the standard test method ASTM D4607-14 or the same industrial test, such as Calgon Carbon Corporation Test TM-4. Note that weight iodine number is sometimes referred to as iodine number.
[0065] As used herein, “molasses number by weight” or “molasses number” means the complete test procedure for determining the decolorization capacity of an adsorbent or adsorbent material according to Calgon Carbon Method TM-3 entitled “Determination of the Molasses Number of Activated Carbon,” which is fully described herein. Molasses number by weight is reported as a unitless quantity measured per mass of adsorbent or adsorbent material.
[0066] Adsorbents (and therefore their associated housings and systems) can be used to purify coolants, such as those contaminated during use. For example, one or more components of data center building materials (e.g., polymers, metals) may leach into the coolant. In another instance, the coolant may react with one or more components of the building materials to produce reaction products that can contaminate the coolant. These conductive contaminants can increase the conductivity of the coolant and thus pose a risk to the operation of electronic components. Therefore, systems can be implemented to remove such conductive contaminants. Consequently, this document provides assemblies and methods for purifying coolants, such as for purifying coolants in immersion cooling applications.
[0067] Such assemblies include a container configured to contain a coolant and an adsorbent within a housing, the housing being configured to contact the adsorbent with the coolant. The assembly can be included, for example, in a system for immersion cooling, such as an immersion cooling system for data centers or other electronic components requiring cooling. Figure 1 The depicted system 100 may include a tank 102 filled with a volume of coolant 104, electronic components 106, and a housing 110 including an adsorbent. The top of the coolant 104 forms a surface 108 corresponding to the level to which the coolant 104 is filled in the tank 102.
[0068] Examples of suitable adsorbents for the methods and apparatus assemblies disclosed herein include, but are not limited to, carbonaceous carbon, activated carbon, reactivated carbon, natural and synthetic zeolites, silica, silica, carbon nanotubes, and graphene. Preferably, the adsorbent comprises activated carbon, which will be used below as an example to illustrate various aspects of the methods and apparatus assemblies suitable for purifying coolants. However, any method and apparatus assemblies described below can utilize any of the adsorbents listed above without departing from the methods and systems contemplated and disclosed herein.
[0069] In any embodiment, the adsorbent may include activated carbon. Activated carbon can be obtained from any known source, such as, but not limited to, bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nuts, macadamia nuts, palm nuts, peach pits, cherry pits, olive pits, walnut shells, wood, bagasse, rice husks, corn husks, wheat husks, polymers, resins, petroleum bitumen, other carbonaceous materials (e.g., extruded pellets), or any combination thereof. Commercially available sources of activated carbon include, but are not limited to, ACTICARBONE® activated carbon (available from Calgon Carbon), such as BGX, which is a granular activated carbon derived from wood / plant sources and activated with phosphoric acid, RB (also available from Calgon Carbon), which is activated carbon derived from coal, or activated carbon from Kuraray (e.g., KURARAY COAL).
[0070] In any embodiment, the adsorbent (activated carbon or others) may be provided in powder, granule, or agglomerate form. For example, activated carbon may be provided in powder or granule form, such as (but not limited to) re-agglomerated carbon powder, or pulverized particles produced by processing (e.g., crushing, grinding, etc.) the materials listed above. As used herein, granular activated carbon (GAC) refers to activated carbon particles of a size that can be retained on a 50-mesh sieve (approximately 0.300 mm pores). As used herein, powdered activated carbon (PAC) refers to activated carbon particles that pass through an 80-mesh sieve (approximately 0.180 mm pores).
[0071] Activated carbon can be formed by methods well known in the art, such as by carbonization and activation or by direct activation. For example, raw materials such as wood, nutshells, coal, asphalt, etc., can be oxidized and devolatiles removed using gasified steam and / or carbon dioxide to form a porous structure in the carbonaceous material, thereby creating adsorption sites. The oxidation and devolatiles removal process may involve chemical treatment, for example, with dehydrating chemicals such as phosphoric acid, boric acid, sulfuric acid, sodium hydroxide, potassium hydroxide, or combinations thereof.
[0072] The performance of the adsorbent in a liquid coolant can be improved when one or more of its moisture content and / or oxygen content is reduced. To reduce the moisture content, the adsorbent can be exposed to an absolute pressure less than the approximate pressure of the surrounding atmosphere, for example less than about 101,325 Pa (about 101 kPa at sea level) or close to a vacuum. Alternatively, or in addition to exposing the adsorbent to the aforementioned reduced pressure, the adsorbent can be heated to a temperature of about 100°C, about 125°C, about 150°C, about 175°C, or about 200°C, or a range formed by one or more of these temperatures.
[0073] In some embodiments, the adsorbent or adsorbent material may be calcined to remove oxygen. Calcination is a process well known in the art and can be carried out in an inert environment at temperatures from about 500°C to about 1000°C. Calcination can be carried out at temperatures of about 500°C, about 550°C, about 600°C, about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, about 900°C, about 950°C, about 1000°C, or in any range having an endpoint corresponding to one or more of the above temperatures.
[0074] By controlling the steam injection rate, temperature, residence time, and content of the activating gas (e.g., steam, carbon dioxide, etc.), the adsorbent material can be activated to the desired apparent density, molasses number, and iodine number. Those skilled in the art will be able to determine suitable activation conditions and optimize them as needed to provide an adsorbent with the desired disclosed properties.
[0075] For example, adsorbents suitable for the methods and systems disclosed herein, such as activated carbon, can exhibit an adsorption capacity of approximately 0.2 g / cm³. 3 Approximately 1 g / cm 3 For example, approximately 0.3 g / cm³ 3 To approximately 0.7 g / cm 3 Approximately 0.2 g / cm 3 To approximately 0.4 g / cm 3 Or approximately 0.2 g / cm 3 To approximately 0.5 g / cm 3The apparent density. Alternatively, the adsorbent, such as activated carbon, may exhibit an iodine number of at least about 800 mg / g, such as about 800 mg / g to about 2000 mg / g, about 900 mg / g to about 1500 mg / g, or about 1000 mg / g to about 1500 mg / g, or about 900 mg / g, about 1000 mg / g, about 1100 mg / g, about 1200 mg / g, about 1300 mg / g, about 1400 mg / g, about 1500 mg / g, about 1600 mg / g, about 1700 mg / g, about 1800 mg / g, about 1900 mg / g, or about 2000 mg / g. Suitable adsorbents, such as activated carbon, can be characterized by the following: at least about 150, such as about 150 to about 200 (e.g., if coconut-based), about 200 to about 600 (e.g., if coal-based), or about 1000 to about 6000 (e.g., if wood-based) molasses number by weight, or about 150, about 160, about 170, about 180, about 190, about 200, about 210, about 220, about 230, about 240, about 250, about 260, about 270, about 280, 290, about 300, about 350, about 400, about 450, about 500, about 550, about 600, about 650, about 700, about 750, about 800. The weight molasses number is approximately 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, or 3000, or any range between two or more of the values listed above, or any range of values at least greater than any of the foregoing values, such as at least about 150, at least about 200, at least about 250, at least about 300, at least about 350, or at least about 400. The weight molasses number of the calcined adsorbent may be higher than that of the uncalcined adsorbent. Activated charcoal with a molasses count of at least about 150 from any source is covered by this disclosure and is suitable for use in the methods and systems disclosed herein.Suitable adsorbents according to this disclosure, such as, but not limited to, activated carbon, have a moisture content of less than about 15 wt.%, less than about 14 wt.%, less than about 13 wt.%, less than about 12 wt.%, less than about 11 wt.%, less than about 10 wt.%, less than about 9 wt.%, less than about 8 wt.%, less than about 7 wt.%, less than about 6 wt.%, less than about 5 wt.%, less than about 4.5 wt.%, less than about 4.0 wt.%, less than about 3.5 wt.%, less than about 3.0 wt.%, less than about 2.5 wt.%, less than about 2.0 wt.%, less than about 1.5 wt.%, less than about 1.0 wt.%, less than about 0.5 wt.%, or about 15 wt.%, about 14 wt.%, about 13 wt.%, about 12 wt.%, about 11 wt.%, or about 10 wt.%. The percentages are approximately 9 wt.%, approximately 8 wt.%, approximately 7 wt.%, approximately 6 wt.%, approximately 5 wt.%, approximately 4.5 wt.%, 4.0 wt.%, approximately 3.5 wt.%, approximately 3.0 wt.%, approximately 2.5 wt.%, approximately 2.0 wt.%, approximately 1.5 wt.%, approximately 1.0 wt.%, or approximately 0.5 wt.%, or approximately 0.1 wt.%, or any range formed by two or more of the foregoing values as endpoints. In some embodiments, as determined by ASTM D2862-16 (or its equivalent), less than approximately 5 wt.% of the adsorbent (regardless of origin) has a particle size of 40 mesh (US) or 0.425 mm or less. Additionally, the ash content of a suitable adsorbent may not exceed approximately 23 wt.%. The ash content of a suitable adsorbent can be, for example, about 23% or less, such as about 20% or less, about 15% or less, about 10% or less, 5% or about 3% or less.
[0076] In any embodiment, the adsorbent, such as activated carbon, may be treated to desorb or react (oxidized) surface products, the presence of which can be measured by any known method, such as by X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), elemental analysis, temperature-programmed desorption, Fourier-transform infrared (FTIR) spectroscopy, Boehm titration, water adsorption, moisture balance, or determining the mass difference of activated carbon before and after drying, or any combination thereof.
[0077] In any embodiment, an adsorbent material with a reduced oxygen content (in terms of bulk oxygen or surface oxygen) can be formed by calcining the precursor adsorbent material at at least about 500°C, for example, about 500°C to about 1000°C, or any value within this range, such as about 500°C, about 550°C, about 600°C, about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, about 900°C, about 950°C, or about 1000°C. After calcination, the adsorbent material is cooled in an inert atmosphere. The calcination process is the primary driver of reducing moisture and bulk oxygen in the resulting adsorbent, while cooling the adsorbent in an inert atmosphere serves to substantially prevent the reintroduction of moisture or oxygen into the adsorbent after calcination. The calcination process is not limited and includes exposing the adsorbent to at least one of the aforementioned temperatures described in this paragraph in an inert atmosphere. The inert atmosphere is not limited, as long as it does not result from additional surface functions or activities of the adsorbent. Examples of such inert atmospheres include one or more rare gases, such as helium, neon, argon, krypton, and xenon, and under certain conditions without imparting catalytic function, the inert atmosphere may be nitrogen, and in some embodiments, calcination may be carried out under vacuum.
[0078] For example, the adsorbent may be provided after being purged under nitrogen to remove oxygen-containing surface groups or moisture. Optionally, the adsorbent may be packaged and provided in a vacuum-filled housing, which may be done, for example, according to the method disclosed in U.S. Patent No. 6,131,368, which is incorporated herein by reference in its entirety. For example, the adsorbent may be heated within an impermeable packaging material (e.g., a bag) and then cooled under nitrogen to create a sufficient vacuum within the packaging material, at which point the packaging material may be hermetically sealed. For example, in any embodiment where the adsorbent comprises activated carbon, the carbonaceous material may be heated to about 500°C to about 1000°C in an inert atmosphere for a desired amount of time, then cooled to 100°C in an inert atmosphere, packed into a packaging material in an inert atmosphere, and then further cooled and sealed, still in an inert atmosphere.
[0079] The bulk oxygen content of the adsorbent material should be limited to avoid reaction between the adsorbent material and conductive contaminants in the coolant. For example, the bulk oxygen content may not exceed about 15 wt.%, not exceeding about 14 wt.%, not exceeding about 13 wt.%, not exceeding about 12 wt.%, not exceeding about 11 wt.%, not exceeding about 10 wt.%, not exceeding about 9 wt.%, not exceeding about 8 wt.%, not exceeding about 7 wt.%, not exceeding about 6 wt.%, not exceeding about 5 wt.%, not exceeding about 4 wt.%, not exceeding about 3 wt.%, not exceeding about 2 wt.%, or not exceeding about 1 wt.%. For example, the bulk oxygen content may be within the following ranges: about 1 wt.% to about 15 wt.%, about 1 wt.% to about 10 wt.%, or about 1 wt.% to about 5 wt.%.
[0080] This disclosure further provides a method for purifying a coolant with an adsorbent as described above, the method comprising contacting the coolant with the adsorbent under conditions that effectively transfer conductive contaminants in the coolant to the adsorbent (e.g., by absorption or adsorption). Examples of suitable adsorbents suitable for the methods and systems disclosed herein include, but are not limited to, carbonaceous carbon, activated carbon, reactivated carbon, natural and synthetic zeolites, silica, silica, carbon nanotubes, and graphene. For example, a suitable adsorbent, such as activated carbon, can exhibit a purity of about 0.2 g / cm³. 3 Approximately 1 g / cm 3 For example, approximately 0.3 g / cm³ 3 To approximately 0.7 g / cm 3 Approximately 0.2 g / cm 3 To approximately 0.4 g / cm 3 Or approximately 0.2 g / cm 3 To approximately 0.5 g / cm 3The apparent density. Alternatively, the adsorbent, such as activated carbon, may exhibit an iodine number of at least about 800 mg / g, such as about 800 mg / g to about 2000 mg / g, about 900 mg / g to about 1500 mg / g, or about 1000 mg / g to about 1500 mg / g. Suitable adsorbents, such as activated carbon, may be characterized by a molasses number of at least about 150, such as about 150 to about 250 (e.g., if coconut-based), about 330 to about 600 (e.g., if coal-based), or about 1000 to about 6000 (e.g., if wood-based). The moisture content of suitable adsorbents may also be less than about 15%, such as less than about 10%, less than about 2.5%, or about 0.01% to about 2.5%. Preferably, as determined by ASTM D2862-16 (or its equivalent), less than about 5 wt.% of the adsorbent (regardless of origin) has a particle size of 40 mesh (US) or 0.425 mm or less. Additionally, the ash content of a suitable adsorbent may not exceed about 23 wt.%. Suitable adsorbents may have an ash content of, for example, about 23% or less, such as about 20% or less, about 15% or less, about 10% or less, 5% or about 3% or less.
[0081] To effectively contact the coolant with the adsorbent, the adsorbent can be provided in a form suitable for passive or active filtration of the coolant. For example, return Figure 1 The adsorbent can be provided in cartridge form for use in conjunction with housing 110, allowing for cartridge replacement as needed. Housing 110 may include inlet 114 and outlet 116 for actively delivering coolant through the adsorbent cartridge within housing 110. Those skilled in the art will recognize methods and apparatus suitable for delivering coolant through an adsorbent filter using a pump. For example, any pump commonly used as an automotive fuel pump can be used. Alternatively, the housing itself may be coolant-permeable, for example, having perforated walls, where coolant can passively contact the adsorbent. This configuration may be particularly useful where a smaller volume of coolant is required and the diffusion of conductive contaminants to the filter is sufficient to remove them. Optionally, the housing may additionally contain or be connected to a size-restricted filter downstream of the adsorbent to capture any adsorbent material swept out of the effluent from the housing including the adsorbent. For example, the filter may be about 325 mesh to about 40 mesh, such as about 200 mesh to about 40 mesh, about 100 mesh to about 40 mesh, or about 80 mesh to about 40 mesh. As used herein, mesh size corresponds to US size, where 325 mesh corresponds to an aperture size of 44 µm, 200 mesh corresponds to an aperture size of approximately 75 µm, 100 mesh corresponds to an aperture size of approximately 150 µm, 80 mesh corresponds to an aperture size of approximately 180 µm, and 40 mesh corresponds to an aperture size of approximately 425 µm.
[0082] The adsorbent can be provided in the casing in an amount approximately two to three times the expected mass of contaminants in the coolant, less than amounts currently recommended in the art. For example, the total mass of elastic material to be contacted by the coolant can be aggregated, and then it can be assumed that between approximately 0.1% (if relatively clean) and approximately 25% (in extreme cases) of that mass are contaminants that may permeate into the coolant. In any embodiment, for example, approximately 200 g of adsorbent can be used to remove conductive contaminants from up to approximately 800 L of coolant. In any embodiment, the method for purifying the coolant can include removing the adsorbent and replacing it with fresh adsorbent. Optionally, the adsorbent, particularly in embodiments where the adsorbent comprises activated carbon, can be reactivated or calcined by any method known in the art.
[0083] Immersion cooling systems, equipment assemblies, and the adsorbents contained therein are not particularly limited to compatible coolants and can be used to purify any coolant suitable for cooling electronic components. Those skilled in the art will be familiar with a variety of useful coolants and their desired properties. Typically, immersion cooling utilizes single-phase or two-phase cooling systems to dissipate heat generated by electronic components. In single-phase cooling systems, the coolant is typically provided in a liquid phase and remains in the liquid phase throughout the cooling process, using convection, mechanical agitation, or a combination thereof to dissipate energy transferred from the electronic components to the coolant. The direction of energy flow (from or to the device) is determined by the relative energy (i.e., temperature) difference between the device and the heat transfer mechanism. In two-phase systems, the coolant is also typically provided in liquid form. Heat generated at the surface of the electronic components is transferred to the liquid coolant, causing it to evaporate and form bubbles that rise to the surface of the liquid coolant. A condenser located above the surface of the liquid coolant can operate at a temperature below the condensation temperature of the rising vapors, thereby condensing the evaporated coolant back into its liquid phase.
[0084] In any application, a suitable coolant for cooling electronic components can have a sufficiently low dielectric constant and conductivity to avoid any circuit problems with the electronic components. For example, a suitable coolant may have a dielectric constant (e.g., as determined by ASTM D924) of less than about 10 (e.g., from about 0.1 to about 10), preferably less than about 7.5 (e.g., from about 0.1 to about 7.5). A suitable coolant may also have a resistivity (e.g., as determined by ASTM D257-14) of less than about 10. 8 Ω·cm to approximately 10 15 Ω·cm.
[0085] Additionally, the coolant can have sufficient thermal conductivity and specific heat to transfer energy away from electronic components, as well as a viscosity that allows the coolant to move freely. For example, a suitable coolant may have a specific heat (e.g., as determined by ASTM E1269-11 (2018)) of about 1000 J / kg·K to about 1350 J / kg·K. A suitable coolant may have a thermal conductivity (e.g., as determined by ASTM D2717-86) of about 0.05 W / m℃ to about 0.5 W / m℃. A suitable coolant may have a kinematic viscosity (e.g., as determined by ASTM D341-77) of no more than about 0.80 cSt, such as about 0.25 cSt to about 0.80 cSt.
[0086] For example, coolants suitable for single-phase cooling systems can exhibit high atmospheric boiling points. In two-phase cooling systems, the boiling point of the coolant can be below the operating surface temperature of the electronic components (to ensure evaporation at the interface), but above the ambient operating temperature to ensure that most of the coolant remains in the liquid phase during typical operating conditions. For example, suitable coolants for two-phase systems may have boiling points of approximately 34°C to approximately 175°C, approximately 40°C, approximately 45°C, approximately 50°C, approximately 55°C, approximately 60°C, approximately 65°C, approximately 70°C, approximately 75°C, approximately 80°C, approximately 85°C, approximately 90°C, approximately 95°C, approximately 100°C, approximately 105°C, approximately 110°C, approximately 115°C, approximately 120°C, approximately 125°C, approximately 130°C, approximately 135°C, approximately 140°C, approximately 145°C, approximately 150°C, approximately 155°C, approximately 160°C, approximately 165°C, approximately 170°C, or approximately 175°C. The coolant in a two-phase system can also exhibit a high latent heat of evaporation.
[0087] The coolant can be a single fluid or a mixture of fluids. Examples of suitable coolants include, but are not limited to, oils (e.g., mineral oil, vegetable oil, castor oil, silicone oil), ketones and perfluorinated ketones (e.g., NOVEC 649 or NOVEC 774 sold by 3M Company), hydrocarbons and perfluorinated hydrocarbons (e.g., FC-72, FC-84, FC-3284, FC-3283, FC-40 sold by 3M Company), polyphenylene ether or hydrofluoroether (HFE) fluids (e.g., SANTOVAC 5 pump fluid, NOVEC 7000, NOVEC 7100, NOVEC 7200, NOVEC 7300, NOVEC 7500, or NOVEC sold by 3M Company). 7700), hydrofluoroether olefins (HFEO), hydrofluoroolefins (HFO), hexafluoropropylene trimers (e.g., as disclosed in U.S. Patent No. 10,662,359, which is incorporated herein by reference in its entirety, including its disclosure of trimers), diphenyl ethers / biphenyl, or any mixture thereof. In some embodiments, the coolant is filtered through a size exclusion filter.
[0088] Immersion cooling systems utilizing adsorbents as disclosed herein can further include components beyond those listed above. Figure 1 As shown, coolant 104 and electronic components 106 are contained within a tank 102, which may be made of welded metal (e.g., carbon steel, aluminum, stainless steel) or glass and is insulated to prevent heat loss. The tank may be large enough to hold sufficient coolant to cool the electronic components therein. For example, the tank may be about 500 L, about 550 L, about 600 L, about 650 L, about 700 L, about 750 L, about 800 L, about 850 L, about 900 L, about 950 L, or about 1000 L. In a two-phase cooling system 200, as... Figure 2 As shown, a tank 202 is provided with a volume of coolant 204 and electronic components 106 contained therein. Also contained within the tank 202 is a housing 110 containing an adsorbent. The housing 110 may include an inlet 114 and an outlet 116, and in some embodiments, the housing 110 may be connected to a pump 112. In the two-phase cooling system 200, the evaporated coolant 226 rising to the coolant surface 208 will create a vapor headspace above the coolant surface 208, referred to as a vapor zone 218. The two-phase cooling system 200 may therefore additionally include a condenser 220 located within the vapor zone 218 to reliquefy the evaporated coolant. The two-phase system may also include a desiccant 222 to collect water that migrates to the headspace 224 above the vapor zone. The desiccant 222 may therefore be located above the vapor zone 218 and provided in an amount sufficient to collect the desired amount of water, such as at least five times the desired water mass.
[0089] In any of the configurations disclosed herein, there is a possibility that adsorbent particles may be entrained in the coolant when the coolant comes into contact with the adsorbent. Therefore, it is contemplated that the system described herein optionally includes at least one size exclusion filter that removes or otherwise prevents adsorbent particles from entering the coolant during coolant flow. The immersion cooling system and equipment assembly may additionally include pressure control, for example, via bellows connected to mechanical and pressure switches controlling solenoid valves, and pumps, heat sources, heat sinks, refrigeration systems, active or passive temperature control systems, heat exchangers, or any combination thereof for controlling fluid levels.
[0090] A method for purifying a coolant for electronic components is provided, the method comprising: contacting the coolant with an adsorbent, wherein the adsorbent is characterized by a molasses number of at least 330 by weight.
[0091] In some embodiments, the adsorbent is activated carbon.
[0092] In some embodiments, the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, wood, peat, nut shells, fruit pits, coconut, babassu nuts, macadamia nuts, palm nuts, peach pits, cherry pits, olive pits, walnut shells, wood, bagasse, rice husks, corn husks, wheat husks, polymers, resins, petroleum bitumen, and other carbonaceous materials.
[0093] In some embodiments, the adsorbent is formed by calcining carbonaceous material at a temperature of at least about 500°C under an inert atmosphere.
[0094] In some embodiments, the apparent density of the adsorbent is about 0.2 g / cm³. 3 Approximately 1 g / cm 3 .
[0095] In some embodiments, the iodine number of the adsorbent is at least about 850 mg / g.
[0096] In some embodiments, the iodine number of the adsorbent is at least about 1100 mg / g.
[0097] In any embodiment, the moisture content of the adsorbent is less than about 15 wt.%.
[0098] In some embodiments, the adsorbent has been treated to remove oxygen-containing surface groups.
[0099] In some embodiments, the process for removing oxygen-containing surface groups includes one or more of the following: purging the adsorbent with an inert atmosphere; placing the adsorbent in a housing containing an oxygen removal compound; and mechanically removing oxygen from the housing containing the adsorbent.
[0100] In some embodiments, the process includes purging the adsorbent with an inert atmosphere.
[0101] In some embodiments, the coolant includes one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof.
[0102] In some embodiments, the coolant has a boiling point of about 34°C to about 175°C and a dielectric constant of less than about 10 at 1 kHz.
[0103] In some embodiments, the kinematic viscosity of the coolant does not exceed about 0.8 cSt.
[0104] In some embodiments, the electronic component is a printed circuit board (PCB).
[0105] In some embodiments, the method further includes contacting the electronic components with a coolant.
[0106] In some embodiments, the method further includes conveying the effluent from the housing containing the adsorbent through a size exclusion filter.
[0107] A system for purifying a coolant for electronic components is provided, the system comprising a coolant and a housing including an adsorbent, wherein the housing is configured to contact the adsorbent with the coolant, wherein the adsorbent is characterized by a molasses number of at least 330.
[0108] In some embodiments, the adsorbent has been purged with nitrogen to remove oxygen-containing surface groups.
[0109] In some embodiments, the adsorbent is inertly filled or vacuum-filled in the housing.
[0110] In some embodiments, the system further includes a pump that delivers coolant through an adsorbent.
[0111] In some embodiments, the coolant includes one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof.
[0112] In some embodiments, the coolant has a boiling point of about 34°C to about 175°C, a freezing point of about -38°C to about -138°C, and a dielectric constant of less than about 10 at 1 kHz.
[0113] In some embodiments, the electronic components are housed within the data center.
[0114] In some embodiments, the system further includes a size exclusion filter connected downstream of the housing that includes the adsorbent.
[0115] Example Before describing the examples, the test method should be fully described.
[0116] Determination of the weight of molasses To determine the molasses number by weight, Calgon Carbon Corporation Test Method Number TM-3 (“TM-3”) was used. TM-3 is designed to determine the decolorizing ability of activated carbon. The decolorizing ability of activated carbon describes its pore structure and material transport. The molasses number by weight was determined according to TM-3.
[0117] Limitations: The concentration of the molasses solution used for testing depends on the standard carbon. As used herein, "standard carbon" refers to the activated carbon adsorbent material, which is a reference material for the characteristics of the molasses number by weight. As will be understood by those skilled in the art, "200 standard carbons" can be expected to produce a molasses number of 200 by weight, "250 standard carbons" can be expected to produce a molasses number of 250 by weight, and so on. 200 standard carbons must be used for activated carbon products predicted to have a molasses number of less than 230 by weight. 250 standard carbons must be used for activated carbon products predicted to have a molasses number of less than 350 by weight. 400 standard carbons must be used for activated carbon products predicted to have a molasses number of 350 or greater by weight. Whenever the molasses specification range of the product includes a range of molasses standard carbons, the higher molasses standard carbon should be used. In these cases, it is appropriate to include the molasses standard carbon to be used in the product specification as a description of the manufacturing process. The molasses solution cannot be diluted. A fixed optical path length of 2.5 mm must be used.
[0118] As will be understood by those skilled in the art, standard carbon is not limited, provided that it is a reference material applicable to the molasses number. One example of 400 standard carbon is “RB,” which is available from Calgon Carbon Company in Moon Township, PA. RB is a powdered steam activated carbon made from bituminous coal with a minimum iodine number of 1070 mg / g, a molasses number of 400, a maximum ash content of 23 wt.%, a maximum moisture content of 2 wt.%, and having 60 wt.% to 75 wt.% particles screened at 325 mesh or smaller than 44 µm. A second example of 320 standard carbon is “RC,” which is also available from Calgon Carbon Company in Moon Township, PA. RC is a powdered steam-activated carbon made from bituminous coal with a minimum iodine number of 1020 mg / g, a molasses number of 320, a maximum ash content of 23 wt.%, a maximum moisture content of 2 wt.%, and containing 60 wt.% to 75 wt.% particles screened at 325 mesh or smaller than 44 µm. A third example of 230 standard carbon is “BL,” available from Calgon Carbon Company in Moontown, Pennsylvania. BL is a powdered steam-activated carbon made from bituminous coal with a minimum iodine number of 1000 mg / g, a molasses number of 230, a maximum ash content of 10 wt.%, a maximum moisture content of 2 wt.%, and containing 60 wt.% to 75 wt.% particles screened at 325 mesh or smaller than 44 µm.
[0119] Method Principle: A molasses solution is treated with carbon of unknown decolorizing ability and standard carbon having the molasses number described above. Higher standard carbon is used to measure the value in the flat portion of the decolorization curve, such as... Figure 3 As shown. The absorbance of the filtrate was determined using a standard spectrophotometer with a wavelength of 472 nm and a path length of 2.5 mm. The molasses number of the sample was calculated as the ratio of the absorbance values of the sample to those of the standard carbon.
[0120] Safety Precautions: Always handle with care and use good laboratory techniques when working with laboratory equipment. Personnel performing this test should be aware of the potential safety hazards associated with the equipment used in this procedure.
[0121] The instruments used in TM-3 are described in Table 1 below: Table 1
[0122] The reagents used in TM-3 are described in Table 2 below: Table 2
[0123] The molasses solution is prepared according to the following procedure: 1. Weigh about 50 grams of molasses into a clean, dry beaker and set aside until the water is heated to 95°C.
[0124] 2. Using a graduated measuring cylinder, add 1000 mL of ASTM Type 2 water to a stainless steel beaker.
[0125] 3. Cover the beaker with aluminum foil or a large glass lid, place it on a hot plate, and heat it to 95°C.
[0126] 4. When the water reaches 95°C, transfer the weighed molasses to a stainless steel beaker and stir to mix thoroughly. Remove the stainless steel beaker from the hot plate.
[0127] 5. Cool the solution to room temperature (approximately 25°C).
[0128] 6. Siphon the molasses solution from the stainless steel beaker into a suitable container. Place a piece of TYGON tubing in the beaker so that the end of the tubing is one inch from the bottom of the beaker. Use a pipette bulb to begin siphoning. Siphon the solution into a separate container (e.g., a large glass bottle).
[0129] 7. Discard the remaining contents of the beaker. Store the molasses solution in the refrigerator for up to 24 hours. Keep the molasses solution on ice while running the assay.
[0130] 8. Weigh 0.46 ± 0.0002 g of 250 molasses standard carbon into a clean, dry 400 mL beaker.
[0131] 200 and 250 standard carbon standardization 9. Transfer 50 mL of molasses solution into a beaker. While adding the molasses solution, vortex the beaker until the carbon is completely wetted.
[0132] 10. Place the beaker on a hot plate and place the thermocouple / thermometer inside the beaker with its tip resting on the bottom of the beaker. Heat the solution until the thermocouple / thermometer reaches 98°C and the stopwatch starts. Remove the thermocouple or thermometer and allow the solution to boil for 30 seconds.
[0133] 11. Filter the sample through a Buchner funnel under vacuum using the previously prepared Whatman® No. 3 filter paper. Cover the filtrate with approximately 20 mL of solution and discard this filtrate. Filter the remainder.
[0134] 12. Measure and record the absorbance of the filtrate at a wavelength of 472 nm on a spectrophotometer using a 2.5 mm fixed path cell. The solution is considered normalized when the absorbance is between 0.630 and 0.650.
[0135] 13. When the absorbance is greater than 0.650, the solution is considered too dark. To determine the amount of water to add, measure the volume of the molasses solution and multiply it by 0.640, and then multiply by the absorbance recorded in step 12. Subtract the numbers, and the result is the amount of water to add to the molasses solution (in milliliters). Add the water and mix the solution thoroughly. Repeat steps 8-13 until the absorbance values of three consecutively analyzed samples are between 0.630 and 0.650.
[0136] 14. When the absorbance is less than 0.630, the solution is considered too bright. To determine the amount of molasses to add, measure the volume of the molasses solution and multiply it by 0.640, and then multiply by the absorbance recorded in step 12. Subtract the two numbers, divide the result by 10, and use the result as the amount (by weight) of molasses to add to the small glass beaker. Add approximately 25 mL of molasses solution to the beaker to dissolve the molasses. Heat the beaker to 90°C on a hot plate and then cool it slightly. Add the contents to the molasses solution and mix thoroughly. Repeat steps 8-14 until three consecutive samples are obtained with absorbance values between 0.630 and 0.650.
[0137] 400 Standard Carbon Standardization 15. Weigh 0.46 ± 0.0002 g of 400 molasses standard carbon into a clean, dry 400 ml beaker.
[0138] 16. Transfer 50 mL of molasses solution into a beaker. While adding the molasses solution, vortex the beaker until the carbon is completely wetted.
[0139] 17. Place the beaker on a hot plate and place the thermocouple / thermometer inside the beaker with its tip resting on the bottom of the beaker. Heat the solution until the thermocouple / thermometer reaches 98°C and the stopwatch starts. Remove the thermocouple or thermometer and allow the solution to boil for 30 seconds.
[0140] 18. Filter the sample through a Buchner funnel under vacuum using the previously prepared Whatman® No. 3 filter paper. Cover the filtrate with approximately 20 mL of solution and discard this filtrate. Filter the remaining 30 mL and use it for subsequent measurements.
[0141] 19. Measure and record the absorbance of the filtrate at a wavelength of 472 nm on a spectrophotometer using a 2.5 mm fixed path cell. The solution is considered normalized when the absorbance is between 0.390 and 0.410.
[0142] 20. When the absorbance is greater than 0.410, the solution is considered too dark. To determine the amount of water to add, measure the volume of the molasses solution and multiply it by 0.400, and then multiply by the absorbance recorded in step 19. Subtract the numbers, and the result is the amount of water to add to the molasses solution (in milliliters). Add water and mix the solution thoroughly. Repeat steps 15-20 until three consecutive samples are obtained with absorbance values between 0.390 and 0.410.
[0143] 21. When the absorbance is less than 0.390, the solution is considered too bright. To determine the amount of molasses to add, measure the volume of the molasses solution and multiply by 0.400, and then multiply by the absorbance recorded in step 19. Subtract the two numbers, divide the result by 10, and the result of the division is the amount (by weight) of molasses to add to the small glass beaker. Add approximately 25 mL of molasses solution to the beaker to dissolve the molasses. Heat the resulting solution to 90°C on a hot plate and then cool it slightly. Add the contents of the molasses solution and mix thoroughly. Repeat steps 15-21 until three consecutive samples are obtained with absorbance values between 0.390 and 0.410.
[0144] Optionally, beakers are standardized. Beaker standardization aims to identify and eliminate beakers whose boiling times differ significantly from other beakers used in the test. Eliminating these beakers will improve in-laboratory accuracy. When the supplier is unable to supply consistent beakers over time, a new average should be established for all beakers tested. The average should not include those beakers that exceed three (3) standard deviations.
[0145] The beakers were standardized according to the following procedure: 1. Identify all beakers using numbers or other specific markings.
[0146] 2. Using a 50 mL pipette, add 50 mL of deionized water / distilled water to a 400 mL beaker for standardized use in TM-3.
[0147] 3. Place the beaker on the hot plate and insert the thermocouple or thermometer so that it is at the bottom of the beaker, and start the stopwatch.
[0148] 4. Measure the time required for the water in the beaker to reach 95°C, and record the time to the nearest second.
[0149] 5. Determine the average time for standardization of the beaker group.
[0150] 6. Beakers with a time difference of ±20 seconds from the average can be used for sample analysis and standardization in TM-3.
[0151] 7. Beakers outside the 20-second range cannot be used to analyze samples or standards for TM-3.
[0152] The sample was analyzed according to the following procedure: 1. Provide a sample of carbon and grind it until 95% or more of the molasses passes through a 325-mesh sieve. If the sample is not from a recent production, dry it to a constant weight at 150°C before use. Prepare standard carbon internals in the same manner. Grind equal amounts to ensure comparable material fineness.
[0153] 2. Weigh 0.46 ± 0.0002 g of the dried pulverized carbon sample into a separate, clean, and dry 400 mL beaker.
[0154] 3. Prepare the filtration setup for sample filtration. Place the Whatman® No. 3 filter ring in the Buchner funnel. Connect the funnel to a 250 mL filter flask and start vacuum filtration. Add 50 mL of filter paper suspension, ensuring it coats the entire surface of the filter paper ring. After draining all liquid, discard the filtrate collected in the filter flask.
[0155] 4. Transfer 50 mL of standardized molasses solution into a beaker containing the carbon to be analyzed. While adding the molasses solution, vortex the beaker until the carbon is completely wetted.
[0156] 5. Place the beaker on a hot plate and place the thermocouple or thermometer inside the beaker with its tip resting on the bottom. Heat the solution until the thermocouple reading reaches 98°C and the stopwatch starts. Remove the thermocouple or thermometer and allow the solution to boil for 30 seconds.
[0157] 6. Using the Whatman® No. 3 filter paper prepared earlier according to step 3, filter the sample through a Buchner funnel under vacuum. Cover the filter with approximately 20 mL of sample and discard this filtrate. Filter the remainder.
[0158] 7. Measure and record the absorbance of the filtrate at a wavelength of 472 nm on the spectrophotometer using a 2.5 mm fixed-path Klett™ Summerson cell. Use deionized water or distilled water as a reference.
[0159] 8. The number of molasses is calculated as follows: Number of molasses = (A × B) / C Where A is the molasses number of the standard carbon (250 or other); B is the average absorbance of three measurements for the 250 standard carbon or other standard carbon; and C is the absorbance of the filtrate of the activated carbon being analyzed.
[0160] 9. Report the molasses count as the nearest increment in tens using standard rounding techniques. (e.g., 2²⁶ = 2³⁰) Determination and neutralization of contact pH To determine the contact pH, Calgon Carbon Test Method TM-62 (“TM-62”) was used. This method is designed to measure the pH of water in static contact with granular activated carbon at a weight ratio of 1 part carbon to 4 parts water. It can also determine the requirements for neutralization mixtures. The determination of the contact pH is performed as described below.
[0161] 1. Weigh a representative portion of 25.0 g of granular activated carbon sample and place it in a 400 ml beaker. Unless the sample is from a recent product, dry the sample at 150°C for 3 hours before use and cool it to room temperature in a desiccator.
[0162] 2. Add 100 ml of reagent water. The reagent water is described as ASTM D 1193 Type 111. Recently boiled distilled or deionized water generally meets the requirements for Type 1111 water.
[0163] 3. Add the magnetic stir bar and stir the mixture on a slow speed for 5 minutes.
[0164] After 4.5 minutes, stop stirring and allow the carbon to settle for 1 minute. 5. Place the electrode in the solution and read the pH value. Report this pH value as "Contact pH".
[0165] After measuring the contact pH, an optional neutralization experiment can be performed by acid or base titration until the endpoint pH of 7 is reached. According to the TM-62 method, the following steps are performed: 1. While stirring the mixture, titrate slowly with an appropriate reagent. The endpoint is pH 7, achieved over approximately one minute. If the contact pH > 7, use 0.10 N HCl. If the pH < 7, use 0.10 N NaOH.
[0166] 2. Report the "mL of reagent" required to achieve neutralization.
[0167] Determination of pH and neutralization of carbon suspension filtrate This method aims to determine the amount of acid (0.004 N HCl) or base (0.004 N NaOH) required to titrate a filtrate produced by filtering 25 g of particulate carbon suspension, which had been added to 100 mL of deionized water and gently agitated in a temperature-controlled water bath at 25°C for 24 hours. After 24 hours, the particulate carbon suspension was filtered using gravity or vacuum filtration. The initial pH of the filtrate was measured. If the initial pH of the filtrate was >7, 0.004 N HCl was slowly titrated into the filtrate until the pH endpoint of 7 was reached. The volume of 0.004 N HCl required to neutralize the filtrate was recorded. Using this information, those skilled in the art can compare the basicity of different types of carbon. As will be understood by those skilled in the art, the stronger the basicity of a carbon, the more acid is required to neutralize its filtrate.
[0168] Conversely, if the initial pH of the filtrate is <7, slowly titrate 0.004 N NaOH into the filtrate until the pH endpoint of 7 is reached. Record the volume of 0.004 N NaOH required to neutralize the filtrate. Using this information, the acidity of different carbons can be compared. The stronger the acidity of a carbon, the more acid is required to neutralize its filtrate.
[0169] Determining the zero charge point pH using mass titration The zero charge point (PZC) of carbon, pH, is referred to as pH in this paper. PZC, This describes the pH at which the net surface charge of carbon is zero. If comparing two carbons, the pH... PZC A higher pH value indicates a more alkaline carbon surface. Conversely, if comparing two carbons, the pH value indicates a more alkaline surface. PZC Lower carbon content results in a more acidic property. The zero-charge point pH is based on the method described in "Valdes H. et al., 'Effect of Ozone Treatment on Surface Properties of Activation Carbon', Langmuir, Vol. 18, 2002, pp. 2111-2116", the entire contents of which are incorporated herein by reference. To determine the pH... PZC Follow the procedure below: 1. Three different 0.1 N sodium nitrate (NaNO3) were prepared by adding an appropriate amount of sodium nitrate to boiled deionized water.
[0170] 2. Adjust the pH of the 0.1 N sodium nitrate solution to 3, 6, or 11 by adding a small amount of 0.1 N nitric acid or sodium hydroxide.
[0171] 3. For each solution with a different pH, add 40 ml of the solution to a set of seven 50 ml centrifuge tubes.
[0172] 4. For each group of seven centrifuge tubes containing pH-adjusted sodium nitrate solution, granular carbon was added to achieve carbon concentrations of 0.1, 1.0, 5.0, 10.0, 15.0, and 20.0 wt%. The seventh tube contained no carbon and was included in the analysis as a blank.
[0173] 5. After adding carbon to the solution, gently agitate the carbon suspension in a temperature-controlled water bath at 25°C for 24 hours.
[0174] 6. After 24 hours, remove the solution from the water bath and allow the carbon to precipitate for about an hour.
[0175] 7. Next, use a pH probe to measure the pH of each carbon suspension. Check the "blank" solution to ensure consistent pH over a 24-hour period.
[0176] 8. For a set of samples using solutions with pH 3, 6, or 11, the pH was plotted as a function of carbon mass. Then, the pH of the carbon was... PZC The value was defined as the point at which the measured pH of each of the three sample groups had stabilized. This stable pH was expected to be generally the same, regardless of the initial pH of the sodium nitrate in which the carbon was suspended.
[0177] Thermogravimetric analysis (TGA) The carbon sample was placed in a TGA apparatus (TA Instruments TGA 500) and inertly heated under a nitrogen flow, while the sample was heated from approximately 25°C to 900°C. The mass loss of the sample was measured during heating using a sensitive balance in the apparatus. Samples containing moisture may lose mass at temperatures up to approximately 100°C, and other surface oxides may be expelled from the sample as CO or CO2 in the range of approximately 200°C to 900°C. Therefore, those skilled in the art can compare the types of surface oxygen or the amount of moisture in a sample by examining the relative degree of mass loss between two types of carbon (such as raw activated carbon, which may have been naturally oxidized, and a calcined version of that raw material). Carbon that has undergone a high-temperature calcination process may have lost some moisture and surface oxygen during this process, and therefore will lose less mass in the TGA compared to an uncalcined raw material of the same material.
[0178] Elemental oxygen analysis The “bulk” oxygen content of activated carbon samples can be measured using an elemental analyzer. In this context, bulk oxygen is defined as any oxygen that can be present throughout the entire sample, rather than the oxygen that can only be measured in the first few nanometers of the carbon surface, as determined by complementary techniques such as X-ray energy dispersive spectroscopy (XPS). The bulk oxygen content of various dry carbon samples was determined using an Elementar varioEl cube, which heats the sample to a high temperature and uses an infrared detector to determine the oxygen concentration. Using this apparatus, those skilled in the art can compare the differences in oxygen content between calcined and uncalcined activated carbon.
[0179] Determination of the moisture content of activated carbon To determine the moisture content of activated carbon samples, Calgon Carbon Company Test Method TM-1 (“TM-1”) was performed. This TM-1 test is identical to ASTM D2867.
[0180] Determination of the iodine number in activated carbon To determine the iodine count of the activated carbon samples, Calgon Carbon Company Test Method TM-4 (“TM-4”) was performed. This TM-4 test is identical to ASTM D4607.
[0181] Determination of ash content in activated carbon To determine the ash content of the activated carbon samples, Calgon Carbon Company Test Method TM-5 (“TM-5”) was performed. This TM-5 test is identical to ASTM D2866.
[0182] Determination of the apparent density of activated carbon To determine the ash content of the activated carbon samples, Calgon Carbon Company Test Method TM-7 (“TM-7”) was performed. This TM-5 test is identical to ASTM D2854.
[0183] Example 1 – Compatibility of Various Activated Carbons Various activated carbons from diverse sources and prepared using various methods were screened for use as adsorbents in purification coolants, as shown in Table 3 below. BGX is a wood-based granular activated carbon with an N2BET or adsorption specific surface area of approximately 1550-1650 m². 2 / g, ash content is 2.5 wt.%, and the density of the substituted product is about 0.24 g / cm³. 3And it is available from Calgon Carbon Company in Moontown, Pennsylvania. RB is a coal-based powdered activated carbon with an iodine number of at least 1070 mg / g, an ash content of no more than 23 wt.%, a moisture content of no more than 2 wt.%, and a wet screen mesh size of approximately 60-75 wt.% -325 US mesh, and is available from Calgon Carbon Company in Moontown, Pennsylvania.
[0184] Table 3
[0185] The specific drying procedure is as follows: None: Remove the filter media from the supplied container and test it.
[0186] Vacuum: Add approximately 100 grams of filter media to a 4-ounce glass jar. Next, cover the jar opening with three KIMWIPES® (cellulose wipes for fine tasks) and secure them in place with two types of rubber adhesive. Place the lidded jar in a vacuum oven. Apply a vacuum and heat the sample to 180°C. Dry for 24 hours or until the pressure in the vacuum oven is less than 100 mTorr (13.33 Pa), indicating that drying is complete. Allow the oven to cool to room temperature under vacuum. When at room temperature, purge the chamber to atmospheric pressure with dry nitrogen, remove the KIMWIPES®, replace the jar, and wrap the lid with vinyl tape. Then store the sample in a dry N2 chamber.
[0187] N2 / Furnace: Add approximately 50 grams of filter media to a 4-ounce glass jar. Place the full jar (without the lid) in a muffle furnace and close the door. Set the nitrogen flow to 90 SCFH and purge the furnace for 10 minutes. Then reduce the nitrogen flow to 20 SCFH and heat the furnace to 180°C. Dry at 180°C for 16 hours. Remove the jar from the oven at 180°C, cover it, and allow it to return to room temperature. Then store the sample in a dry N2 chamber.
[0188] Air / Solvent Oven: Air drying was performed in a ventilated solvent oven. Approximately 50 grams of filter media was added to a 4-ounce glass jar. The jar (without a lid) was placed in a ventilated solvent oven and heated to 180°C. Drying was carried out for 16 hours. The jar was removed from the oven at 180°C and the lid was replaced, then allowed to return to room temperature. The sample was then stored in a dry N2 oven.
[0189] Inert atmosphere calcination / kiln: Kiln calcination in an inert atmosphere. Approximately 0.5 kg of activated carbon is added to a rotary kiln. The activated carbon is treated at 950°C under an inert nitrogen atmosphere for 20 minutes. The calcined activated carbon is then discharged into a nitrogen-containing chamber and inertly cooled to approximately 100°C. The activated carbon is then inertly filled into a nitrogen-purged container or vacuum-filled in a manner that minimizes exposure to air.
[0190] Example 2 – Moisture Content As described in Table 4, the compatibility of various activated carbons from different sources with varying moisture contents as adsorbents was screened.
[0191] Table 4
[0192] Example 3 Larger calcination experiments were conducted using a rotary kiln, in which coal-based “RB” activated carbon was calcined at approximately 980°C under a nitrogen atmosphere for up to 30 minutes. After calcination, the carbon was allowed to cool under a nitrogen atmosphere and then inertly packaged. Table 5 below compares some properties of the calcined RB with those of its laboratory-dried (typically at 150°C for 3 hours) or untreated feedstock (denoted as F / S). Calcinated RB is referred to as “calcined RB”, dried RB feedstock as “dry F / S RB”, and untreated RB feedstock as “F / S RB”.
[0193] In Table 5, calcination of the carbon achieved a low moisture content of 0.2 wt.%, a level that cannot be achieved by drying alone. The advantages of the calcination process are also evident when observing the bulk oxygen level, which is 1.6% for the calcined RB. This is approximately 2-fold less than that of the F / S RB and 1.5-fold less than that of the dried F / S RB. Furthermore, the increased contact pH of the calcined RB relative to other RB samples to 10.4 indicates an increase in carbon basicity resulting from the calcination process, which removes surface oxygen groups or other acidic moieties present in the carbon. While not wishing to be bound by theory, low moisture content, oxygen content, and surface acidity are believed to be key characteristics of activated carbon for immersion cooling applications. Table 5 shows that high-temperature calcination produces activated carbon products with these inherent characteristics without significantly altering the transport structure of the raw carbon, as indicated by relatively small changes in iodine and molasses numbers.
[0194] Table 5
[0195] The calcination of granular wood-based activated carbon was carried out in a laboratory setting, where the raw material F / S BGX was calcined at approximately 950°C under a nitrogen atmosphere for 30 minutes. After calcination, the activated carbon was cooled to ambient temperature under a nitrogen atmosphere. It was then stored in an inert environment. This calcined version of F / S BGX is referred to as calcined BGX. Data for an air-dried version of F / S BGX were also collected and are indicated as dried F / S BGX where appropriate. This version of activated carbon was prepared by air-drying F / S BGX at 150°C for 3 hours. The physical and chemical properties of these wood-based materials are described in Table 6.
[0196] Table 6
[0197] In Table 6, the calcined BGX samples achieved a very low moisture level of less than 0.1 wt.%. Further advantages were achieved through calcination, as the bulk oxygen concentration of the calcined BGX samples was approximately 50% lower than that of the dried F / S BGX samples and approximately 65% lower than that of the F / S BGX samples. Additionally, the contact pH of the calcined BGX was 7.3, almost neutral, compared to the acidic pH of 4.0 measured for the dried F / S BGX samples. The increase in contact pH of the calcined BGX samples indicates a significant reduction in surface acidity due to the presence of fewer surface oxygen groups and possibly other acidic components. The data in Table 6 also show that the calcination process maintained the highly inherent porous structure of F / S BGX, as the molasses number of the calcined BGX material exceeded 1500. This high molasses number indicates a well-developed transport pore structure. Furthermore, the iodine number of the calcined BGX samples also exceeded 1000, a characteristic of activated carbon with significant total surface activity. The pore structure and surface activity exhibited by calcined BGX, combined with its very low moisture content, low oxygen content and reduced surface acidity, are considered key advantages when using wood-based activated carbon for submerged cooling applications.
[0198] For the samples listed in Table 5, TGA analysis was performed. Table 7 describes the mass loss data for calcined RB, dried F / S RB, and F / S RB after TGA treatment. In Table 7, the total mass loss of the calcined RB sample was only 1.50 wt.%, while the values for the dried F / S RB and F / S RB samples were 1.91 and 2.38 wt.%, respectively. Since the calcined RB sample exhibited the smallest change in total mass percentage after TGA treatment, this indicates that calcination produces a more inert activated carbon with less moisture and fewer surface functional groups that can escape from the activated carbon during the TGA experiments. Conversely, the dried F / S RB and F / S RB materials contained more intrinsic moisture and surface functional groups than the calcined RB, and therefore lost more mass during the corresponding TGA experiments.
[0199] Table 7
[0200] Table 8 describes the mass loss (wt.%) of calcined BGX, dried F / S BGX, and F / S BGX after treatment in TGA. The total mass loss of the calcined BGX sample was only 9.35 wt.%, while the values for the dried F / S BGX and F / S BGX samples were 12.60 and 35.50 wt.%, respectively. The calcination process produces a more pristine activated carbon surface than drying alone, and therefore the calcined RB exhibits a smaller total mass loss after TGA treatment due to its inherently lower moisture levels and surface fractions that may have escaped during analysis. For this wood-based activated carbon, calcination appears to be particularly effective in removing entrained moisture (in the 25°C to 200°C range) and surface oxides or other surface functional groups in the 200°C to 600°C range. Although the difference in mass loss between dried and calcined F / S BGX was not significant within the temperature range of 600°C to 900°C, the smaller mass loss exhibited by calcined BGX still highlights the importance of calcination at high temperatures to remove additional surface oxygen or other functional groups. Therefore, the calcination of activated carbon feedstock F / S BGX yields an enhanced wood-based product, calcined BGX, whose properties are particularly suitable for immersion cooling applications.
[0201] Table 8
[0202] Table 9 describes the contact pH and amount of 0.1 N hydrochloric acid (HCl) required to neutralize carbon suspensions of calcined RB, dried F / S RB, or F / S RB as described in TM-62. Here, when titrating the calcined RB suspension, nearly 10 mL more of 0.1 N HCl is required to reach the pH 7 endpoint compared to dried F / S RB, indicating a more alkaline activated carbon. The titration data, combined with the higher contact pH of calcined RB, enhances its increased alkalinity due to the elimination of the acidic portion from the carbon surface during calcination.
[0203] Table 9
[0204] Table 10 describes the required pH and amount of 0.1 N NaOH for neutralizing carbon suspensions of calcined BGX and dried F / S BGX as described in TM-62. In Table 10, the contact pH for calcined BGX is 6.7, and only 0.9 mL of 0.1 N NaOH is needed to reach the pH 7 endpoint, while the dried F / S BGX sample has a significantly more acidic contact pH of 4.0 and requires 48.5 mL of alkali to reach its titration endpoint. This indicates that the calcination process produces activated carbon products with reduced acidity, even if the activated carbon raw material is inherently acidic due to its manufacturing method (as in the case of BGX).
[0205] Table 10
[0206] Table 11 describes the titration of filtrates obtained from aqueous suspensions of dried F / SRB and calcined RB. Here, 40 mL of filtrate was titrated with 0.004 N HCl. The initial pH of the calcined RB filtrate was 10.5, and 12.5 mL of acid was required to reach the pH endpoint of 7, compared to only 2.8 mL required for titrating the dried F / SRB filtrate, because its filtrate had a lower initial alkalinity of 9.8. This titration data and the difference in initial filtrate pH between the two materials reflect the increased alkalinity of the calcined activated carbon relative to the dried activated carbon.
[0207] Table 11
[0208] Table 12 describes the titration of filtrates obtained from aqueous suspensions of dried F / S BGX and calcined BGX. The filtrate obtained from the calcined BGX suspension had an initial pH of 7.8, slightly alkaline, and required 16.8 mL of 0.004 N HCl to reach the final pH of 7. Conversely, the filtrate obtained from the dried F / S BGX suspension had an initial pH of 4.7, significantly more acidic. This filtrate required 68 mL of 0.004 N NaOH to reach the titration endpoint pH. The data in Table 12 indicate that even for inherently acidic activated carbon like BGX (due to its manufacturing method), calcination induces a significant shift of the activated carbon surface to a neutral or alkaline state, which is advantageous for this application.
[0209] Table 12
[0210] Thermal processes such as calcination can affect the surface properties of activated carbon, which in turn can affect its pH. PZC For RB and BGX activated carbon, a relatively large pH was measured after calcination. PZC The value indicates an increase in the alkaline (basic) properties of the activated carbon surface. The calcination process removes surface groups containing acidic oxygen.
[0211] Figure 5 The average pH measurements of dried F / S RB or calcined RB sodium nitrate suspensions at common activated carbon concentrations of 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.% are shown. An asymptotic pH of approximately 11.5 was observed as the wt.% of dried F / S RB activated carbon increased to 15 and 20 wt.%. PZC Value. Alternatively, as the amount of calcined RB increased to 20 wt.%, the average suspension pH still increased. This means that the pH of calcined RB... PZC It's at least 11.8, but possibly higher. Figure 5 Data shows that calcination of F / S RB activated carbon enhances surface alkalinity, thereby improving its performance in immersion cooling applications.
[0212] Figure 6 The average pH measurements of dried F / S BGX or calcined BGX sodium nitrate suspensions at common activated carbon concentrations of 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.% are shown. An asymptotically acidic pH of approximately 4.5 was observed as the wt.% of dried F / S BGX activated carbon increased to 20 wt.%. PZC Alternatively, when the amount of calcined BGX reached 20 wt.%, the recorded average pH decreased, but stabilized at a near-neutral pH of approximately 6.5. PZC value. Figure 6 Data shows that calcination of F / S BGX activated carbon slightly reduces its surface acidity, thereby improving its performance in immersion cooling applications.
[0213] In the above detailed description, reference has been made to the accompanying drawings, which form a part thereof. In the drawings, similar symbols generally identify similar components unless the context otherwise requires. The illustrative embodiments described in the detailed description, drawings, and claims are not intended to be limiting. Other embodiments may be used, and other changes may be made, without departing from the spirit or scope of the subject matter set forth herein. It will be readily understood that, as generally described herein and shown in the accompanying drawings, aspects of this disclosure can be arranged, substituted, combined, separated, and designed in a variety of different configurations, all of which are expressly contemplated herein.
[0214] This disclosure is not limited to the specific embodiments described herein, which are intended as illustrative of various aspects. Many modifications and variations of the technology of this invention can be made without departing from the spirit and scope of the invention, as will be apparent to those skilled in the art. In addition to those listed herein, functionally equivalent methods and apparatuses within the scope of this disclosure will be apparent to those skilled in the art based on the foregoing description. Such modifications and variations are intended to fall within the scope of the appended claims. This disclosure is limited only by the terms of the appended claims and the entire scope of their authorized equivalents. It should be understood that this disclosure is not limited to specific methods, reagents, compounds, compositions, or systems, although these can vary. It should also be understood that the terminology used herein is for the purpose of describing specific embodiments only and is not intended to be limiting.
[0215] Regarding the use of virtually any plural and / or singular terms in this document, those skilled in the art can convert plural to singular and / or singular to plural as appropriate to the context and / or application. For clarity, various singular / plural permutations may be explicitly described herein.
Claims
1. A method for purifying a coolant containing one or more conductive contaminants, the method comprising: The coolant is brought into contact with the adsorbent, thereby causing the adsorbent to adsorb the one or more conductive pollutants, wherein the adsorbent comprises an adsorbent material having a bulk oxygen content of 1 wt.% to 5 wt.%, a moisture level of up to 1.5 wt.%, a contact pH of 6.5 to 12, and a molasses number of at least 150. The adsorbent material mentioned above includes activated carbon.
2. The method according to claim 1, wherein the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, peat, nut shells, fruit kernels, coconut, babassu nut, macadamia nut, dende nut, wood, bagasse, rice husk, corn husk, wheat husk, polymer, and petroleum bitumen.
3. The method according to claim 1, wherein the activated carbon is formed from one or more of the following: peach pits, cherry pits, olive pits, walnut shells, and resin.
4. The method according to claim 1, wherein the adsorbent material is formed by calcining a carbonaceous material at a temperature of at least 500°C under an inert atmosphere.
5. The method according to claim 1, wherein the weight iodine number of the adsorbent material is at least 850 mg / g.
6. The method according to claim 5, wherein the weight iodine number of the adsorbent material is at least 1100 mg / g.
7. The method of claim 1, wherein the adsorbent has been treated to prevent the reintroduction of oxygen.
8. The method of claim 7, wherein treating the adsorbent to prevent the reintroduction of oxygen comprises one or more of the following: purging the adsorbent material with an inert atmosphere; placing the adsorbent in a housing containing an oxygen removal compound; and mechanically removing oxygen from the housing containing the adsorbent.
9. The method of claim 1, wherein the coolant comprises one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof.
10. The method of claim 1, wherein the coolant has a boiling point of 34°C to 175°C and a dielectric constant of less than 10 at 1 kHz.
11. The method of claim 1, wherein the kinematic viscosity of the coolant does not exceed 0.8 cSt.
12. The method of claim 1, further comprising contacting the electronic component with the coolant and allowing conductive contaminants to diffuse from the electronic component into the coolant.
13. The method of claim 1, further comprising filtering the coolant through a size-restricted filter.
14. A system for purifying a coolant containing one or more conductive contaminants, the system comprising: A shell containing an adsorbent comprising an adsorbent material having a bulk oxygen content of 1 wt.% to 5 wt.%, a moisture level of up to 1.5 wt.%, a contact pH of 6.5 to 12, and a molasses number of at least 150. At least one inlet, or at least one outlet, or at least one inlet and at least one outlet, in communication with the adsorbent, and a tank containing the coolant, such that at least a portion of the coolant is in contact with the adsorbent.
15. The system of claim 14, wherein the adsorbent comprises an adsorbent material that is itself activated carbon.
16. The system of claim 15, wherein the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, peat, nut shells, fruit pits, coconuts, babassu nuts, macadamia nuts, palm nuts, wood, bagasse, rice husks, corn husks, wheat husks, polymers, and petroleum bitumen.
17. The system of claim 15, wherein the activated carbon is formed from one or more of the following: peach pits, cherry pits, olive pits, walnut shells, and resin.
18. The system of claim 14, wherein the adsorbent material is formed by calcining a carbonaceous material at a temperature of at least 500°C under an inert atmosphere.
19. The system of claim 14, wherein the weight iodine number of the adsorbent material is at least 850 mg / g.
20. The system of claim 19, wherein the weight iodine number of the adsorbent material is at least 1100 mg / g.
21. The system of claim 14, wherein the adsorbent has been purged with nitrogen to prevent the reintroduction of oxygen.
22. The system of claim 14, wherein the adsorbent is inertly filled or vacuum-filled in the housing.
23. The system of claim 14, further comprising a pump for delivering the coolant through the adsorbent.
24. The system of claim 14, wherein the coolant comprises one or more of the following: oil, hydrocarbon, ketone, ether, or any fluorinated derivative thereof.
25. The system of claim 14, wherein the coolant has a boiling point of 34°C to 175°C, a freezing point of -38°C to -138°C, and a dielectric constant of less than 10 at 1 kHz.
26. The system of claim 14, wherein the kinematic viscosity of the coolant does not exceed 0.8 cSt.
27. The system of claim 14, further comprising electronic components containing one or more conductive contaminants.
28. The system of claim 27, wherein the electronic components are housed within a data center.
29. The system of claim 14, further comprising a size exclusion filter connected downstream of the housing including the adsorbent.
30. A composition for purifying a coolant containing one or more conductive contaminants, said composition comprising: An adsorbent comprising an adsorbent material having a bulk oxygen content of 1 wt.% to 5 wt.%, a moisture level of up to 1.5 wt.%, a contact pH of 6.5 to 12, and a molasses number of at least 150, wherein the adsorbent material comprises activated carbon.
31. The composition of claim 30, wherein the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, peat, nut shells, fruit kernels, coconut, babassu nuts, macadamia nuts, palm nuts, wood, bagasse, rice husks, corn husks, wheat husks, polymers, and petroleum bitumen.
32. The composition according to claim 30, wherein the activated carbon is formed from one or more of the following: peach pits, cherry pits, olive pits, walnut shells, and resin.
33. The composition of claim 30, wherein the weight iodine number of the adsorbent material is at least 850 mg / g.
34. The composition of claim 33, wherein the weight iodine number of the adsorbent material is at least 1100 mg / g.
35. The composition of claim 30, wherein the adsorbent has been treated to prevent the reintroduction of oxygen.
36. A method for preparing an adsorbent for purifying a coolant containing one or more conductive contaminants, the adsorbent comprising an adsorbent material, the method comprising: The calcined precursor adsorbent material is formed by having a main oxygen content of 1 wt.% to 5 wt.%, a moisture level of up to 1.5 wt.%, a contact pH of 6.5 to 12, and a molasses number of at least 150. The adsorbent material mentioned above includes activated carbon.
37. The method of claim 36, wherein the activated carbon is formed from one or more of the following: bituminous coal, sub-bituminous coal, lignite, anthracite, peat, nut shells, fruit pits, coconuts, babassu nuts, macadamia nuts, palm nuts, wood, bagasse, rice husks, corn husks, wheat husks, polymers, and petroleum bitumen.
38. The method of claim 36, wherein the activated carbon is formed from one or more of the following: peach pits, cherry pits, olive pits, walnut shells, and resin.
39. The method of claim 36, wherein calcination occurs at a temperature of at least 500°C.
40. The method of claim 36, further comprising treating the adsorbent material to prevent the reintroduction of oxygen and moisture.
41. The method of claim 40, wherein treating the adsorbent to prevent the reintroduction of oxygen comprises one or more of the following: purging the adsorbent material with an inert atmosphere; placing the adsorbent in a housing containing an oxygen removal compound; and mechanically removing oxygen from the housing containing the adsorbent.
Citation Information
Patent Citations
Heat transfer fluids and methods of using same
US10662359B2
Method for packaging adsorbents
US6131368A
High-performance adsorbents based on activated carbon having high meso- and macroporosity
CN101668587A
Device for recycling alcohol from waste gases through activated carbon adsorption and microwave desorption
CN203425680U
Scavengers for reducing contaminants in liquid-filled LED bulbs
US20130063030A1